Households’ willingness to pay for quality of drinking water in Jaffna area of Sri Lanka - Sooriyakumar, K.; Sumangkalai, P.; Sivashankar, S. (Journal of Water Supply: Research and Technology, 2020)
Jaffna Peninsula of Sri Lanka depends on groundwater for drinking water. Supply of clean drinking water has become limited due to overuse of agrochemicals, widespread use of pit latrines, and seawater intrusion. The aim of this study is to estimate the willingness to pay for the attributes of water quality and supply. One hundred and twenty households were randomly selected in the study area. A choice modeling approach was employed. The result indicates that, on average, households’ willingness to pay for the improvement of water quality is three times higher than their monthly payment. Households are willing to pay more for reduction in calcium than for reduction in nitrate and improvement of other attributes. The education level of households influences willingness to pay for the improvement of water quality more than the income level of households. There is high potential to finance for the improvement of the water quality from the households. Water supply and drainage board can afford to supply the drinking water at the WHO standard and charge price on a volumetric basis. The findings of this study would be useful for policymakers to set the appropriate price and policy to develop a sustainable project.
Keywords: Choice modeling; Conditional logit model; Water quality; Willingness to pay